Thresholds and wearout : A survey of current beliefs and practices - Newall, John; Corkindale, David (Cranfield School of Management, 1977)
This report presents the findings of a survey of advertising beliefs and practices related particularly to the phenomena of 'thresholds' and 'wearout'. The survey was by questionnaire to MCRC sponsors and other interested companies. The answers relate to 23 specific products or services and their advertising. The questionnaire was based upon prior discussion and research among most of the respondents and the literature on the topics which was reported in MCRC Report 12(i).